Meeting in school: Cultural diversity approaches of teachers and intergroup contact among ethnic minority and majority adolescents. Issue 1 (12th September 2022) - Karataş, Savaş; Eckstein, Katharina; Noack, Peter; Rubini, Monica; Crocetti, Elisabetta
Abstract: This study investigated the associations between cultural diversity approaches endorsed by teachers and adolescents' positive and negative intergroup contact in schools. Participants were 984 adolescents ( M age  = 14.66; 62.7% female; 24.8% ethnic minority) involved in a three‐wave longitudinal study between 2019 and 2020. Results highlighted that perceived equal treatment by teachers was related to higher positive and lower negative contact over time. However, perceived support for contact and cooperation and interest of teachers in children's cultural background were not related to either positive or negative contact over time. Importantly, the results were replicated across ethnic minority and majority adolescents. This study provides novel insights into the key role that teachers can play in promoting cultural diversity approaches to facilitate harmonious intergroup interactions in schools.